GREEN INTELLECTUAL CAPITAL: STRATEGI KEUNGGULAN KOMPETITIF (Studi Kasus Pada Badan Usaha Milik Desa Adat Intaran-Sanur) - Anak Agung Putu Gede Bagus Arie Susandya (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Ngurah Rai, 2019)
Green intellectual capital, which is the development of intellectual capital, is a critical component of a business model that emphasizes knowledge and human resources as knowledge assets by paying attention to the surrounding environment. Green intellectual capital is recognized as a new weapon in the development of companies based on eco-friendly concepts. More in-depth analysis of the role of green intellectual capital on competitive advantage in the Indigenous Village Owned Company in Sanur or Badan Usaha Milik Desa Adat (BUMDA). The sample used in this study consisted of 100 respondents from the Indigenous Village Owned Company in Sanur. The analysis technique used is multiple regression analysis techniques. The results of the study found that Green Human Capital, Green Relational Capital, and Green Structural Capital had a significant positive effect on competitive advantage. The results of this study are expected to contribute to the manager of Indigenous Village Owned Enterprises (BUMDA) related to the utilization of green intellectual capital towards BUMDA's competitive advantage compared to other business entities. The increasing concern for the surrounding environment has a positive impact on the competitiveness of the company itself. Competitive advantage is not only obtained from financial figures but also must have a commitment to the environment by the concept of an environmentally-friendly business entity